Comparative study of the damage cost of reinforced concrete buildings with and without nonlinear viscous dampers subjected to seismic loading - Flores-Mendoza, R.; Pozos-Estrada, A.; Gómez, R. (Frontiers in Built Environment, 2022)
In an optimal seismic design context, the seismic demand is characterized with hazard curves that can be obtained by simulation techniques, and the capacity of the structure is established by the designer according to a predefined seismic code. The capacity of structures is generally characterized by the seismic design coefficient. Further, the damage on a structure is evaluated based on some well-defined damage indicators (e.g., based on displacement ductility). Based on the damage indicator, it is possible to estimate the cost of the associated losses. It is noted that the quantification of the damage costs associated with RC structures without and with nonlinear viscous dampers under seismic loading is very scarce in the relevant literature. In this study, damage cost expressions, similar to those employ in the optimal seismic design criterion, are used in order to quantify and compare the damage cost on reinforced concrete (RC) buildings with and without viscous dampers located in seismic prone areas of Mexico. For the analysis, three RC buildings are designed according to Mexican seismic design regulations. The buildings under study are subjected to seismic actions that are characterized by actual seismic records, which were scaled according to simulated maximum ground motion accelerations. The damage to the structures due to seismic action is calculated by means of a damage factor that is a function of displacement ductility demand. The cost of damage to the considered structures was estimated based on cost expressions that are function of the damage factor. The analyses results indicate that the use of viscous dampers in concrete buildings subjected to seismic action can considerably reduce the associated damage costs with respect to buildings without such type of damping system.